Trends in Performance Evaluation of Indonesian Government Structural Officials: A Systematic Review and Bibliometric Analysis - Puti Purnama Sutardjo; Ria Arifianti; Herwan Abdul Muhyi (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Public sector performance evaluation remains a central issue in ensuring bureaucratic effectiveness and accountability. This study aims to systematically map the evolution and intellectual structure of research on the performance assessment of Indonesian government structural officials. Using the PRISMA approach and bibliometric analysis through VOSviewer, 241 Scopus-indexed publications from 2000 to 2025 were analyzed to identify key themes, influential authors, and collaboration networks. The mapping reveals four dominant clusters: governance and organizational performance, employee competence and motivation, policy evaluation and bureaucratic reform, and digital transformation in public management. Research trends show a shift from normative and conceptual approaches toward data-driven, evidence-based evaluation models after 2018. This study offers novel insights by integrating bibliometric visualization with the Heizer performance framework, which links quality, cost, time, flexibility, and productivity as key analytical dimensions. The findings contribute to a deeper understanding of how performance assessment of structural officials has evolved and highlight research gaps relevant to future policy development.